Dolne ograniczenie problemu wyznaczania tras pojazdów przy zadanym podziale odbiorców - Hanczar, Paweł (Lower Bound for Set Partitioning Formulations in Vehicle Routing Problem, 2007)
The lower bound plays a very important role in the solution of combinatorial optimization problems. In the case of usage of heuristic methods, knowledge about lower bound enables the estimation of the quality of achieved solutions. However, in the case of exact methods, particulary in the case of branch and bound methods, the usage of lower bound for the solution subset is one of the algorithms for the solution determination. In this paper we propose a method for finding lower bound for set partitioning formulations of vehicle routing problem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 84-92